2014
DOI: 10.1177/0269216314538302
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the palliative care ‘Availability, Current issues and Anticipation’ (ACA) communication training programme for general practitioners on patient outcomes: A controlled trial

Abstract: Background:Although communicating effectively with patients receiving palliative care can be difficult, it may contribute to maintaining or enhancing patients’ quality of life. Little is known about the effect of training general practitioners in palliative care–specific communication. We hypothesized that palliative care patients of general practitioners exposed to the ‘Availability, Current issues and Anticipation’ communication training programme would report better outcomes than patients of control general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 33 publications
0
25
0
2
Order By: Relevance
“…Training including (self‐)reflection is seen as effective to raise confidence in communicating about existential concerns like DHD . Courses may adapt recommendations for counseling psychologists and include basics in suicide risk assessment as well as practical modules .…”
Section: Discussionmentioning
confidence: 99%
“…Training including (self‐)reflection is seen as effective to raise confidence in communicating about existential concerns like DHD . Courses may adapt recommendations for counseling psychologists and include basics in suicide risk assessment as well as practical modules .…”
Section: Discussionmentioning
confidence: 99%
“…Unter Ärzten, die in onkologischen Abteilungen des Landes Baden-Württemberg arbeiten, gaben lediglich 5,9 % an, dass sie sich durch ihre Berufsausbildung ausreichend gut auf die Begleitung Sterbender vorbereitet sahen [9]. In jüngerer Zeit waren vielfältige Initiativen darum bemüht, spezifisch palliatives Wissen, Fertigkeiten und palliative Haltung bei Studierenden [16] und bei Ärzten der Grundversorgung zu fördern [3,4,8,17,18,20]. Die Begleitevaluation dieser Interventionen erfolgte jeweils unterschiedlich.…”
Section: Hintergrundunclassified
“…Dieses kann mit einem Wissenstest einfach abgefragt werden, was auch in einigen Palliativtests genau so erfolgt [12,15,17]. Die Selbsteinschät-zung der eigenen Fähigkeiten abzufragen, bringt einen Aspekt in die Testung ein, der das fachliche Handeln widerspiegelt [19].…”
Section: Auswahl Der Vorlagen Für Die Testkonstruktionunclassified
“…38 Another randomized trial failed to show an improvement in quality of EOL care as assessed by patients, families, or clinicians after a communication skills training for residents and nurse practitioners. 39 Nevertheless, a recent systematic review showed that advance care planning interventions could improve the satisfaction with EOL care in family members of deceased patients and increase the prevalence and quality of EOLCC.…”
Section: Quality Of Eolccmentioning
confidence: 99%